FACTORS AFFECTING THE FORMATION PROCESS OF AESTHETIC SKILLS IN DRAWING LESSONS - Toshpulatov Fakhriddin Uralovich (International Scientific and Current Research Conferences, 2023)
In this article, the social-pedagogical necessity of developing aesthetic skills of future drawing teachers in drawing classes, the development of creative abilities in the drawing education system, and the formation of aesthetic skills of future drawing teachers are discussed in this article.